2022
DOI: 10.1007/s00405-022-07399-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of occult nodal metastases in squamous cell carcinoma of the temporal bone: a systematic review and meta-analysis

Abstract: Purpose Primary: To determine the rate of occult cervical metastases in primary temporal bone squamous cell carcinomas (TBSSC). Secondary: to perform a subgroup meta-analysis of the risk of occult metastases based on the clinical stage of the tumour and its risk based on corresponding levels of the neck. Methods A systematic review and meta-analysis of papers searched through Medline, Cochrane, Embase, Scopus and Web of Science up to November 2021 to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…As for the management of the neck in SCC of the EAC, elective neck dissection for cN0 patients is still under debate. A recent systematic review and meta-analysis by Borsetto et al [ 38 ] estimated that the rate of occult lymph node metastases in cN0 TBSCC was 14%, with specific subgroup rates of 21% for T3 tumors and 18% for T4 tumors. Metastases were predominantly localized at level II.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the management of the neck in SCC of the EAC, elective neck dissection for cN0 patients is still under debate. A recent systematic review and meta-analysis by Borsetto et al [ 38 ] estimated that the rate of occult lymph node metastases in cN0 TBSCC was 14%, with specific subgroup rates of 21% for T3 tumors and 18% for T4 tumors. Metastases were predominantly localized at level II.…”
Section: Discussionmentioning
confidence: 99%
“…Superficial parotidectomy was advocated to be associated with surgery for early-stage tumors and total parotidectomy for advanced-stage disease [ 15 ]. Although the data is too limited to draw any conclusions on the role of elective neck dissection, increasing evidence indicates that levels Ib to III in cN0 cases should be included [ 18 , 38 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of 267 clinically N0 patients with TBSCC who underwent neck dissection showed that 14% had occult lymph node metastases in the neck. Stratified by Pittsburgh stage, the occult metastasis rate for T1 patients was 0%; the rate for T2 patients was 7% [95% confidence interval (CI): 2–20%]; the rate for T3 patients was 21% (95% CI: 11–38%); and the rate for T4 patients was 18% (CI: 11–27%) [25 ▪ ]. Others base the extent of neck dissection on clinical staging or might perform no neck dissection and opt for postoperative radiotherapy to the neck only [26].…”
Section: Management Of Parotid Disease and The Neckmentioning
confidence: 99%
“…For primary temporal bone cancers, routine elective treatment of the parotid and neck in T 1–2 SCC is not necessary, with occult metastasis rates of 0 and 7 per cent respectively. 948 However, most patients with T 1–2 primary temporal bone SCC will receive surgical treatment, and elective treatment of these nodal basins may be undertaken for surgical access requirements or can be considered part of adjuvant post-operative RT, factoring in histopathology. Elective treatment of the parotid and neck is recommended in T 3–4 primary temporal bone SCC, with occult metastasis rates of around 20 per cent, 948 in keeping with generally accepted practice.…”
Section: Treatmentmentioning
confidence: 99%